Suppression of peptide sample losses in autosampler vials - Stejskal, Karel; Potěšil, David; Zdráhal, Zbyněk (Journal of proteome research, 2013)
Protein or peptide sample losses could accompany all steps of the proteomic analysis workflow. We focused on suppression of sample adsorptive losses during sample storage in autosampler vials. We examined suppression capabilities of six different sample injection solutions and seven types of autosampler vial surfaces using a model sample (tryptic digest of six proteins, 1 fmol per protein). While the vial material did not play an essential role, the choice of appropriate composition of sample injection solution reduced adsorptive losses substantially. The combination of a polypropylene vial and solution of poly(ethylene glycol) (PEG) (0.001%) or a mixture of high concentrated urea and thiourea (6 M and 1 M) as injection solutions (both acidified with formic acid (FA) (0.1%)) provided the best results in terms of number of significantly identified peptides (p < 0.05). These conclusions were confirmed by analyses of a real sample with intermediate complexity (in-gel digest from sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE)). Addition of PEG into the real sample solution proved to prevent higher losses, concerning mainly hydrophobic peptides, during up to 48 h storage in the autosampler in comparison with a formic acid solution and even with a solution of highly concentrated urea and thiourea. Using PEG for several months was not accompanied by any adverse effect to the liquid chromatography system.
Keywords: hydrofobní a hydrofilní interakce; elektroforéza v polyakrylamidovém gelu; adsorpce; Specimen Handling; proteiny; Polyethylene Glycols; Flow Injection Analysis; polyethylenglykoly; průtoková injekční analýza; Thiourea; Peptide Fragments; Hydrophobic and Hydrophilic Interactions; odběr biologického vzorku; Electrophoresis, Polyacrylamide Gel; peptidové fragmenty; chromatografie kapalinová; formiáty; thiomočovina; močovina; Formates; Chromatography, Liquid; Proteins; Adsorption; Urea